The divine names at Dadan: a philological approach - Hidalgo-Chacón Díez, María del Carmen (Proceedings of the Seminar for Arabian Studies, 2016)
Аġbt is the chief deity of the pantheon of Dadanitic inscriptions, most of which are found in the oasis of al-ΚUlā, in north-west Saudi Arabia. According to the inscriptions, Аġbt, as well as other deities such as Κtrġth (ΚAtarΚata, the great goddess of northern Syria, called the Atargatis in the Hellenistic period), were venerated at this oasis. In inscription JSLiΉ 49, there is a curious case in which a priest of the foreign deity Wd, the main god of the Minaeans (an ancient community from the Jawf region, in southern Arabia, modern-day Yemen), makes an offering to the local deity Аġbt. This paper offers an etymology of the deities and considers what some of their spellings tell us about the Dadanitic pronunciation.